Homocysteine May Involve in the Pathogenesis of Behcet's Disease by Inducing Inflammation - Selda Pelin Kartal Durmazlar; Ahmet Akgul; Fatma Eskioglu (Mediators of Inflammation)
Objective. Our aim was to evaluate the significance of homocysteine (Hcy) in Behcet's disease (BD) and the association of elevated Hcy levels associated with the indices of inflammation in BD. Methods. Untreated 70 patients with BD and 33 healthy individuals were included into the study. Hcy, tumor necrosis alpha (TNF-𝛼), C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) were evaluated with respect to activity and specific individual clinical manifestations of the disease. Results. Hcy levels were found significantly elevated in active BD when compared to inactive BD and healthy controls. Hcy levels were found to have high correlation with the number of active clinical manifestations increased. A significant positive correlation was found between serum Hcy and TNF-𝛼 levels, CRP, and ESR. Hcy was found to be the best predictor of TNF-𝛼 among other parameters. Conclusion. Hcy may involve in the pathogenesis of BD by inducing inflammation.